2022
DOI: 10.1002/jclp.23296
|View full text |Cite
|
Sign up to set email alerts
|

Thinking under fire: Mentalization‐based couple therapy for high conflict and domestically abusive couples'

Abstract: Background The question of working psychotherapeutically with high conflict and domestically abusive couples is one that continues to raise anxieties within the field. Aims Embracing a relational approach offers an alternative perspective to the more familiar individual‐based treatment interventions. Materials and Methods Drawing on my therapy with a married couple who presented in a crisis following an abusive incident, I will outline how I approached the assessment, my understanding of their presenting probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the context of women exposed to IPV, a recent study showed evidence of poor mentalization capabilities expressed by reduced abilities in reflecting and ascribing meaning to personal experiences (Condino et al, 2022). The importance of promoting mentalization processes is therefore recommended since it has a possible way of tackling dysregulated states of mind that may lead to act/be exposed to abusive and violent behaviors (Bateman & Fonagy, 2012; McCann, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of women exposed to IPV, a recent study showed evidence of poor mentalization capabilities expressed by reduced abilities in reflecting and ascribing meaning to personal experiences (Condino et al, 2022). The importance of promoting mentalization processes is therefore recommended since it has a possible way of tackling dysregulated states of mind that may lead to act/be exposed to abusive and violent behaviors (Bateman & Fonagy, 2012; McCann, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to develop and apply specialized interventions of various levels, considering the characteristics of the participants or setting (victims/perpetrators/work environments). According to McCann (2022), a mentalization‐based therapy can solve interpersonal conflicts and restore relationships. Therefore, it can be introduced as a new prevention strategy for workplace bullying in nursing management.…”
Section: Discussionmentioning
confidence: 99%